Monetary policy and the drifting natural rate of interest - Sandra Daudignon; Oreste Tristani (European Central Bank (ECB), 2023)
Empirical analyses starting from Laubach and Williams (2003) find that the natural rate of interest is not constant in the long-run. This paper studies the optimal response to stochastic changes of the long-run natural rate in a suitably modified version of the new Keynesian model. We show that, because of the zero lower bound (ZLB) on nominal interest rates, movements towards zero of the long-run natural rate cause an increasingly large downward bias in expectations. To offset this bias, the central bank should aim to keep the real interest rate systematically below the long-run natural rate, as long as policy is not constrained by the ZLB. The neutral rate - the level of the policy rate consistent with stable inflation and the natural rate at its long-run level - will be lower than the long-run natural rate. This is the case both under optimal policy, and under a price level targeting rule. In the latter case, the neutral rate is equal to zero as soon as the long-run natural rate falls below 1%.
Keywords: C63; E31; E52; 330; nonlinear optimal policy; zero lower bound; commitment; liquidity trap; New Keynesian